Economic Migration in Central Siberia and Ethnic Conflict Risks (Based on Krasnoyarsk Krai Analysis) - Kolesnik, Maria A.; Koptseva, Natalia P.; Libakova, Natalia M.; Luzan, Vladimir S.; Sergeeva, Natalia A.; Sertakova, Ekaterina A. (International Journal of Economics and Financial Issues, 2016)
Migration, be it free or forced, is an essential prerequisite of the dynamic development of many territories, Krasnoyarsk Krai inclusive. The territory of the region is irregularly and poorly populated: 84% of inhabitants are concentrated in the south of the region, in the territory comprising only 10% of the regional territory. Under the circumstances Krasnoyarsk Krai needs an increased flow of migrants for the participation in economic development of unpopulated areas of Krai. But on the other hand, economic need in migrants becomes the reason of the ethnic conflicts risks increase in Central Siberia through creation of various negative myths on migrants. The experts report an increase in social tension between migrants and host parties in the Siberian regions of the Russian Federation. The interrelations inside the social medium and cultural contacts are in many respects determinant for the economic development of the region because the main actors of the economics are people. Keywords: economic migration, tolerance index, Siberia, Krasnoyarsk Krai JEL Classifications: D8, R1, Z1